PEMASARAN PRODUK OLAHAN SINGKONG DESA JENGGIK UTARA KECAMATAN MONTONG GADING LOMBOK TIMUR - Basniwati, AD.; Malik, Deni Putra; Akbar, Sand; Rajiburrahman, Rajiburrahman; Nurdiansyah, Andi; Pratiwi, Mita Ayu; Sapitri, Diana; Dimara, Kristi Joy Oktofifteen; Hikmah, Ayu Nurul Hikmah; Humairoh, Tata; Cahayani, Ayu Septina (Universitas Mataram, 2023)
Jenggik Utara is a village located in the Montong Gading District, East Lombok Regency. Jenggik Utara Village is a village rich in cassava products. Residents generally sell cassava directly in the market at a relatively low price. Based on this case, an idea emerged from the KKN students to process cassava into a modern snack. So that socialization and training on processing cassava into a modern snack are tried and carried out product innovation so that products that have high selling value are formed. The implementation of activities is carried out in a participatory manner where all activities involve partners. The series of activities consists of several stages including socialization, manufacturing training, packaging training, and marketing. The outreach activities that have been carried out were successful. Judging from the level of participation of the invited participants, it was 95% of the total invited participants. In terms of the participants' understanding and enthusiasm regarding the material that has been informed, it can be said to be high. Socialization participants are able to make processed products that are well exemplified. So that the training on making processed cassava products can be declared successful. From the participants showing positive reactions related to product labeling and packaging, they felt optimistic that this could increase the selling value of the product itself and make it more desirable in the market. The success indicator of this marketing activity can be seen from the success of selling products, both online and offline. The implementation of the UNRAM Thematic KKN work program with the theme of Preneur Village which was carried out in Jenggik Utara Village which began with product socialization activities, digital marketing and product launching, product manufacturing training, product packaging training, and product marketing has been well implemented.